New Records of the Spider Fauna from Perlis State - Mohtar, Johan Ariff; Abdul Rahman, Khadijah Hanim; Abdul Rahman, Ahmad Mukhlis; Mohamad, Fadhilah (Journal of Sustainable Natural Resources, 2025)
Perlis is endowed with a diverse range of ecosystems supporting a significant flora and fauna biodiversity. Despite its high species richness, few studies have been performed to highlight the diversity of spider species in Perlis. Spider fauna surveys were conducted during Scientific Expeditions at Perlis State Park on 15th – 16th October 2019 and Eco Park Rimba Bukit Ayer on 4th – 6th October 2022. Based on the survey, ten spiders from 41 collected specimens were identified, constituting eight families and nine genera. Out of these, eight genera were identified as new records for Perlis including Nephila, Nephilengys, Orsinome, Pholcus, Psechrus, Heteropoda, Chilobarchys, and Damarchus, with only three being identified at the species level. Overall, the observed spiders are well represented by Araneidae (N = 2), Tetragnathidae (N = 1), Pholcidae (N = 2), Psechridae (N = 1), Liphistidae (N = 1), Sparassidae (N = 1), Theraphosidae (N = 1), and Bemmeridae (N = 1). This baseline data will assist in shedding light on biodiversity and conservation of spider species in Perlis.